Insights into Alternanthera mosaic virus TGB3 Functions: Interactions with Nicotiana benthamiana PsbO Correlate with Chloroplast Vesiculation and Veinal Necrosis Caused by TGB3 Over-Expression - Jang, Chanyong; Seo, Eun-Young; Nam, Jiryun; Bae, Hanhong; Gim, Yeong Guk; Kim, Hong Gi; Cho, In Sook; Lee, Zee-Won; Bauchan, Gary R.; Hammond, John; Lim, Hyoun-Sub (Frontiers in Plant Science, 2013)
Alternanthera mosaic virus (AltMV) triple gene block 3 (TGB3) protein is involved in viral movement. AltMV TGB3 subcellular localization was previously shown to be distinct from that of Potato virus X (PVX) TGB3, and a chloroplast binding domain identified; veinal necrosis and chloroplast vesiculation were observed in Nicotiana benthamiana when AltMV TGB3 was over-expressed from PVX. Plants with over-expressed TGB3 showed more lethal damage under dark conditions than under light. Yeast-two-hybrid analysis and bimolecular fluorescence complementation (BiFC) reveal that A. thaliana PsbO1 has strong interactions with TGB3; N. benthamiana PsbO (NbPsbO) also showed obvious interaction signals with TGB3 through BiFC. These results demonstrate an important role for TGB3 in virus cell-to-cell movement and virus-host plant interactions. The Photosystem II oxygen-evolving complex protein PsbO interaction with TGB3 is presumed to have a crucial role in symptom development and lethal damage under dark conditions. In order to further examine interactions between AtPsbO1, NbPsbO and TGB3, and to identify the binding domain(s) in TGB3 protein, BiFC assays were performed between AtPsbO1 or NbPsbO and various mutants of TGB3. Interactions with C-terminally deleted TGB3 were significantly weaker than those with wild-type TGB3, and both N-terminally deleted TGB3 and a TGB3 mutant previously shown to lose chloroplast interactions failed to interact detectably with PsbO in BiFC. To gain additional information about TGB3 interactions in AltMV-susceptible plants, we cloned 12 natural AltMV TGB3 sequence variants into a PVX expression vector to examine differences in symptom development in N. benthamiana. Symptom differences were observed on PVX over-expression, with all AltMV TGB3 variants showing more severe symptoms than the WT PVX control, but without obvious correlation to sequence differences.